2012
DOI: 10.2478/v10245-012-0017-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of individual plant responsiveness in anther cultures of selected pepper (Capsicum spp.) genotypes

Abstract: One of the key factors determining the effectiveness of pepper anther cultures is donor plant genotype. The stock material for androgenic embryos inductions is usually made up of hybrid forms, since the higher the degree of heterozygosity, the greater the chances of producing regenerates with unique genotypes. The aim of the presented research was to evaluate individual plant reaction in anther cultures for the C. annuum hybrid ('ATZ1' × 'TG')F 2 , interspecific hybrid (C. frutescens × C. chinense)F 2 and andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 18 publications
0
12
0
1
Order By: Relevance
“…Anther culture is a widely used haploidization technique in pepper. Several studies have been carried out on the development of successful protocols related to pepper anther culture (Abak, 1983;Al Remi et al, 2014;Ata, 2011;Buyukalaca et al, 2004;Comlekcioglu et al, 2001;G emesn e Juh asz et al, 2001;George and Narayanaswamy, 1973;Harn et al, 1975;Niklas-Nowak et al, 2012;Novak, 1974;Olszewska et al, 2013;Saccardo and Devreux, 1974;Tas xkın et al, 2011;Wang et al, 1973). In these studies, the rate of spontaneous doubled haploidy was determined via ploidy analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anther culture is a widely used haploidization technique in pepper. Several studies have been carried out on the development of successful protocols related to pepper anther culture (Abak, 1983;Al Remi et al, 2014;Ata, 2011;Buyukalaca et al, 2004;Comlekcioglu et al, 2001;G emesn e Juh asz et al, 2001;George and Narayanaswamy, 1973;Harn et al, 1975;Niklas-Nowak et al, 2012;Novak, 1974;Olszewska et al, 2013;Saccardo and Devreux, 1974;Tas xkın et al, 2011;Wang et al, 1973). In these studies, the rate of spontaneous doubled haploidy was determined via ploidy analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The success of these methods varies according to the species. Positive results in pepper have been achieved with anther culture (Al Remi et al, 2014;Buyukalaca et al, 2004;Comlekcioglu et al, 2001;Ercan et al, 2006;G emesn e Juh asz et al, 2001;Niklas-Nowak et al, 2012;Olszewska et al, 2013;€ Ozkum and Tıpırdamaz, 2002;Tas xkın et al, 2011). The advantage of this method is that there are thousands of microspores in each anther and numerous haploid plants can be obtained from a single anther.…”
mentioning
confidence: 99%
“…These factors include genotype, age of donor plant, pollen development stage, pretreatments made to buds or anthers, and composition of nutrient media. Successful outcomes were achieved with anther culture in pepper (Al Remi et al, 2014;Buyukalaca et al, 2004;Comlekcioglu et al, 2001;Ercan et al, 2006;G emesn e Juh asz et al, 2001;Keles x et al, 2015;Niklas-Novak et al, 2012;Olszewska et al, 2013;Tas xkin et al, 2011), eggplant (Bas xay andEllialtıo glu, 2013;Bas xay et al, 2011), and Brassica spp. (Achar, 2002;Arnison et al, 1990aArnison et al, , 1990bBiddington and Robinson, 1990;G orecka et al, 2007;Phippen and Ockendon, 1990;Roulund et al, 1990).…”
mentioning
confidence: 99%
“…Unfortunately, none are applicable to a wide spectrum of genotypes. For example, Niklas-Nowak et al (2012) established different androgenic response rates even in individual plants belonging to the same genotype. Parra-Vega et al (2013b) obtained a higher percentage of embryos through the shed-microspore approach, compared to conventional anther culture.…”
Section: Introductionmentioning
confidence: 99%
“…In these early studies, the regeneration of plants achieved was of low efficiency, and research efforts in the next experiments aimed to identify the factors influencing induction of androgenesis. After many experiments, it was found that androgenic response depended on the following: growing conditions, age and genotype of the donor plant (Ercan et al, 2006;Niklas-Nowak et al, 2012;Grozeva et al, 2013;KolevaGudeva et al, 2013;Alremi et al, 2014), developmental stage of microspores in the anther (Nowaczyk and Kisiała, 2006;Parra-Vega et al, 2013a;Barroso et al, 2015), composition of the culture medium, concentration and combination of growth regulators, organic and inorganic additives (Büyükalaca et al, 2004;Zhao et al, 2010;Taşkin et al, 2011;Roshany et al, 2013;Olszewska et al, 2014), and pretreatment of flower buds and/or anthers (KolevaGudeva et al, 2007;Özkum and Tıpırdamaz, 2007;Irikova et al, 2011b;Nowaczyk et al, 2015).…”
Section: Introductionmentioning
confidence: 99%